2011
DOI: 10.1007/s13365-011-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical contributors to cerebral white matter integrity in HIV-infected individuals

Abstract: HIV-infected people frequently exhibit brain dysfunction characterized by preferential damage to the cerebral white matter. Despite suppressed viral load and reconstituted immune function afforded by combination antiretroviral therapy (CART), brain dysfunction continues to be observed even in medically stable individuals. To provide insight into the etiology of HIV-associated brain dysfunction in the CART era, we examined the effects of HIV disease markers, antiretroviral treatment, hepatitis C (HCV) coinfecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 47 publications
(57 reference statements)
5
61
4
Order By: Relevance
“…resulted in inconsistent results. Moreover, variations in the studied HIV+ participants in relation to their combination antiretroviral (cART) status, level of viral suppression, the nature of HIV disease , and their demographics (mainly age) (Towgood et al 2012;Chang et al 2008;Gongvatana et al 2011;Seider et al 2015) have probably contributed to a lack of consistency. Altogether, while DTI may be useful at characterizing the extent of WM injury in cases with moderate to severe HIV-associated neurocognitive disorder (HAND) (Chang et al 2008;Chen et al 2009;Gongvatana et al 2011) or advanced untreated HIV infection (Hoare et al 2011;Leite et al 2013;Pfefferbaum et al 2009) (when HIV replication is the cause of the WM damage), its use at elucidating what may be the HIV-related neuropathology substrate in virally suppressed HIV infection is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…resulted in inconsistent results. Moreover, variations in the studied HIV+ participants in relation to their combination antiretroviral (cART) status, level of viral suppression, the nature of HIV disease , and their demographics (mainly age) (Towgood et al 2012;Chang et al 2008;Gongvatana et al 2011;Seider et al 2015) have probably contributed to a lack of consistency. Altogether, while DTI may be useful at characterizing the extent of WM injury in cases with moderate to severe HIV-associated neurocognitive disorder (HAND) (Chang et al 2008;Chen et al 2009;Gongvatana et al 2011) or advanced untreated HIV infection (Hoare et al 2011;Leite et al 2013;Pfefferbaum et al 2009) (when HIV replication is the cause of the WM damage), its use at elucidating what may be the HIV-related neuropathology substrate in virally suppressed HIV infection is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…The volume of the supramarginal gyrus declines in ApoE4 carriers as they convert from mild cognitive impairment to AD (Spampinato et al, 2011). In a diffusion-based study, the regions underlying the gyrus showed suggestive negative associations between FA and age in HIV patients (Gongvatana et al, 2011). Brown et al (2011) also found a significant genetic effect in the supramarginal gyrus.…”
Section: Fig 3 (A)mentioning
confidence: 93%
“…On the other hand, HIV-negative and early HIV-infected (≤1 year of viral exposure) patients exhibit only disruption of the BBB and no significant alterations in WM integrity [248]. Moreover, aging HIV-infected patients exhibit greater WM hyper-intensities and lower fractional anisotropy in the anterior corona radiata due to hepatitis C virus coinfection, the more likely development of AIDS, and higher CD4-positive cell counts as a marker of hyper-activation of inflammatory responses [245, 249]. …”
Section: Relationship Between Brain Structure Alterations and Aging Imentioning
confidence: 99%